Description of the larva of Neuraeschna claviforcipata Martin, 1909 (Insecta: Odonata: Aeshnidae) - Marmels, Jürg De; Neiss, Ulisses Gaspar (Zootaxa, 2013)
The ultimate stadium larva of Neuraeschna claviforcipata is described and illustrated based on an F-0 exuvia of a reared female from northern Amazonas State, Brazil. This larva differs from the other two known larvae of the genus in lacking the spiny lateral prominence of the mandible, and in having only a short spine each side of the median cleft of the prementum; labium is shorter and cercus longer. Noteworthy is the presence of a hair brush on each occipital lobe behind mesal angle of compound eye. The larva was found in a small blackwater pool with abundant leaf litter in an open, “campina”-type habitat, with sandy soil and low, bushy vegetation.